MENAFSIR AHOK DARI PERSPEKTIF ETIKA UTILITARIANISME (Analisis Hermeneutik pada Komunikasi & Tindakan Politik) - Fabianus Fensi (SEMIOTIKA: Jurnal Komunikasi, 2016)
Ahok is the Governor of Jakarta Province that has a style of communication and political action is unique. Communication styles and how to act frankly often rated as a bad action. This study tried to see the other side, namely the use of Ahok’s communication style and political action lead Jakarta. By using the utilitarian ethical theory perspective this study tried to explore the meaning of style led Ahok with instrument hermeneutical interpretation, even archaeological. Starting from this perspective and approach, then discovered that Ahok has a specific purpose with his unique style. Communicate, act, and at the top of the corridor applicable rules Ahok makes a breakthrough on behalf of and for the benefit of a lot of peoples of Jakarta Province. The principle of utilitarianism acts and regulations were given a room in Ahok’s communications and political action. Or, utilitarianism demanding that always strives for happiness as much as possible for as many people got confirmation in Ahok’s action. Low context model communication and political action is the antithesis of Ahok’s disgust to the social system that is permissive to the behavior of the political elite who often manipulate people. On behalf of his rebellion against the hypocrisy of the elite, Ahok goes to ask everything clearly and seemed arogant. Behind it all, it must be admitted, the ordinary people become the main Ahok’s consideration. Key Words: Utilitarianism, Hermeneutics, High Context, Low Context